Some observations on the genus Arthrocnemum - Tölken, H R (Department of Biological Sciences, 2017)
Only in 1954 the notes of late Prof. Moss on the genera Arthrocnemum and Salicornia were published, and although this was a big step forward in the classification of these genera, it proved to be unsatisfactory in many cases. This, however, should not throw the work on that subject done by him into shade, as shows his earlier works (Moss, 1910, 1912, 1914), and only his notes published by Prof. Adamson in 1954 were unfortunately fragmentary. The revision of the genus Arthrocnemum is taken up again, as so many salt marshes on the Cape Flats are drained and the rivers chanalized, so that the number of localities are increasing rapidly, and fresh material is essential for this work. The aim of this work is to cover as large a field as possible, but always with the eye on some further evidence for the taxonomy of the species. Unfortunately, only a few species which are growing on the Cape Peninsula and some fresh material of A. affine from Swakopmund was available for this study. This gives perhaps a bit one-sided view, but indications of similar problems in other species or of difficulties with explaining phenomena has been given for later research. Investigations were mainly done on fresh material, and dried herbarium specimen were usually only consulted for confirming certain characters found in fresh. To aid this it was made use of photos where ever possible, but it was found sometimes almost impossible to get clear pictures, as the flowers are minute and inconspicuous. For convenience, the whole treatise has been divided into three main parts: (1) The ecological part (autecology) in which the zonation phenomenon at Milnerton has been emphasized, but at the same time it gives an account of the particular habitat each species requires. (2) A brief account of the anatomy especially the abnormal secondary growth in the stem and root has been given, and a discussion of the origin of the fleshy segmented branches follows. (3) Lastly the history and the distribution of the whole genus Arthrocnemum, and a treatise of the classification and its difficulties of the species of the Cape Peninsula is produced. This work is purely preliminary, and it is tried to get access not only to the problematic taxonomy, but to an understanding of these plants as such. The author is well aware of some generalisations or speculative assumptions, but the main point of the treatise is to get a new approach to that difficult group of plants, of which each detail seems to be worth to be recorded for later evaluation.